PENGARUH MODIFIKASI ASPAL DENGAN LATEKS PRAVULKANISASI TERHADAP KARAKTERISTIK MARSHALL, KINERJA RENDAMAN, DAN KELELAHAN PADA CAMPURAN BERASPAL PANAS AC-WC - Jimmyanto, Hendrik; Ramadhani, Ramadhani; Lubis, Lega Reskita; Bethary, Rindu Twidi (Universitas IBA Palembang, 2025)
Roads are the primary means of transportation that are essential to support mobility and the distribution of goods and people. As urbanization develops, the increasing vehicle load results in road damage. To address this issue, one potential solution is to modify asphalt using polymer materials such as natural rubber with vulcanized latex. Vulcanized latex, an Indonesian local product, can be used as an additive in asphalt mixtures; however, its use as a main substitute is still limited and primarily supported by empirical and mechanical testing.. The results indicate that mixtures with 7% and 9% vulcanized latex show adequate resistance to soaking, with stability values meeting standards. The inclusion of vulcanized latex at these levels makes the asphalt harder and less elastic, leading to faster fatigue failure, although still within acceptable limits. The use of this material can enhance water resistance but has a negative impact on fatigue life. Therefore, field application must consider a balance between these two aspects to ensure the material's performance remains optimal.